2014
DOI: 10.1111/jvp.12172
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of oral transmucosal and intramuscular dexmedetomidine combined with buprenorphine in cats

Abstract: Plasma concentrations and pharmacokinetics of dexmedetomidine and buprenorphine after oral transmucosal (OTM) and intramuscular (i.m.) administration of their combination in healthy adult cats were compared. According to a crossover protocol (1-month washout), a combination of dexmedetomidine (40 μg/kg) and buprenorphine (20 μg/kg) was given OTM (buccal cavity) or i.m. (quadriceps muscle) in six female neutered cats. Plasma samples were collected through a jugular catheter during a 24-h period. Plasma dexmedet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…Unexpectedly, the results reported in the present study showed a low absorption of both DEX and MET following co-administration TA B L E 3 Median and range of pharmacokinetic parameters calculated with noncompartmental analysis after oral transmucosal (OTM) or intramuscular (IM) simultaneous administration of dexmedetomidine (10 μg/kg) and methadone (0.4 mg/kg) in 12 dogs drug volume that is proportional to the amount of drug administered (Porters et al, 2014).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Unexpectedly, the results reported in the present study showed a low absorption of both DEX and MET following co-administration TA B L E 3 Median and range of pharmacokinetic parameters calculated with noncompartmental analysis after oral transmucosal (OTM) or intramuscular (IM) simultaneous administration of dexmedetomidine (10 μg/kg) and methadone (0.4 mg/kg) in 12 dogs drug volume that is proportional to the amount of drug administered (Porters et al, 2014).…”
Section: Discussionmentioning
confidence: 57%
“…Such a high administration volume could likely have hindered absorption. In fact, according to the results from another study, a high volume of drug administered using the OTM route leads to partial losses during administration and to the swallowing of a drug volume that is proportional to the amount of drug administered (Porters et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations